Reforma del código tributario referente al comercio informal ya que el mismo causa la evasión tributaria en el Ecuador - Lizano Toscano, Mentor Bolibar (2014)
The conceived tributes as all economic benefit demanded in form motivated and proportional by the State to the contributors or people in charge, are constituted in the main source of permanent financing whereupon it counts the general budget of the State, to finance the certain permanent erogacions in the annual pro form approved by the National Assembly, reason by which is necessary an adapted legal regulation that it tries the consolidation of an efficient and sustainable tributary regime. Nevertheless, the existence of informal businesses has been constituted in one of the main problems that effect of the Ecuadorian tributary regime, for being a source of permanent fiscal evasion, in decline of the interests and services public who the State is in the obligation to finance; it is so common to observe in all the sectors from the large city bet people offering services and products without issuing receipt some, nor counting on the suitable permissions or invoices that allow to identify the origin of the merchandise, that has been constituted in a social phenomenon so it frequents like tolerated by all the citizenship. Before this reality and in spite of the high existing indices of commercial unmannerliness in all the cities of the country, a normative regime destined to regulating does not exist at present and as far as possible controlling this type of activities, reason by which and necessary to incorporate within the Tributary Code norms destined to the fulfillment of this aim, because thus it will only be possible to diminish as far as possible this factor and in this way to attenuate the impacts in the national State Treasury. The present work of legal investigation focuses in studying objective and critically the problem of the informal businesses in the corner Rafts and country generally, with the purpose of to establish its causes, incidences and consequences, stops on the basis of it to establish in motivated form a legal proposal that helps to the important solution of this problematic one which it affects the national budget and therefore the society all.